The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/ep.14192
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Direct Orange 46 and phosphate ions on waste tomato stem ash used as a bio‐based adsorbent

Abstract: It is necessary to use adsorbents derived from natural materials, such as biosorbents since they do not any damage to the environment, for pollutants elimination that contaminate the aquatic environment. Since the deficiency in the literature was determined in the study in which only the adsorbent obtained from tomato stem was used before this study, a waste material with tomato stem was selected as a natural adsorbent without chemical compounds. Phosphate and dye contaminants, which are often present in indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(104 reference statements)
1
0
0
Order By: Relevance
“…When evaluating the sorption capacities of different carbonaceous materials, it is imperative to consider these parameters. A large number of previous studies have indicated that the adsorption of ammonium [51][52][53], nitrate [53][54][55][56], and phosphate [57][58][59] is typically exothermic, agreeing with our results (note that the ∆G values obtained in this work are independent of the temperature).…”
Section: Comparison With Other Adsorbentssupporting
confidence: 92%
“…When evaluating the sorption capacities of different carbonaceous materials, it is imperative to consider these parameters. A large number of previous studies have indicated that the adsorption of ammonium [51][52][53], nitrate [53][54][55][56], and phosphate [57][58][59] is typically exothermic, agreeing with our results (note that the ∆G values obtained in this work are independent of the temperature).…”
Section: Comparison With Other Adsorbentssupporting
confidence: 92%